Mediation effect of entrepreneurial attitude between entrepreneurship education and entrepreneurial self-efficacy on entrepreneurial intention evidence from Chinese higher vocational education institutions - Luo Ying; Mohd Faiz Mohd Yaakob (Discover Sustainability)
Abstract Entrepreneurship education significantly impacts students’ entrepreneurial competencies, intentions and behavior. Higher Vocational Education Institutions (HVEIs) play a vital role in China, and they have recorded milestone achievements that foster economic growth and stimulate students’ entrepreneurial mindsets. Applying underpinning theory, this study aims to examine the effect of entrepreneurial education (EE), knowledge (EK) and self-efficacy (ESE) on intention (EI) through the mediating role of entrepreneurial attitude (EA). Using a self-administered survey, cross-sectional design and stratified random sampling technique, this study targeted students enrolled in five HVE institutions in Guizhou, China and collected 416 completed questionnaires. The sorted results revealed that EE positively impacts EI and EA. In contrast, EK and ESE positively impact EI and EA. While this last (EA) positively impacts EI, it also mediates the relationship between EE, EK and ESE on EI. The originality of this study linked the underpinning of entrepreneurship theory with the five supporting theories to explain the relationships among constructs and cover the holistic picture of EE-EI from personnel, environmental and cognitive perspectives. The study recommended that educational managers prioritize developing entrepreneurship curricula and more practices to foster students’ entrepreneurial knowledge and skills for better future entrepreneurial careers. EE is a necessary program, and HVEIs potentially impact the industry and the future of the Chinese economic agenda. This study has several socioeconomic implications and contributes to the Chinese sustainable development agenda.